Social identities, professional identities, teacher identities: multiple representations of itself - Melo, Carlos Ian Bezerra de (2021)
The last decades were marked, in the field of Education, by the directing of discussions in teacher education to the more subjective sphere, understanding the teacher no longer as a mere reproducer of lessons, but as an individual with specificities who becomes a teacher through the socializing processes in the profession. From this context emerges the concept of teacher professional identity (TPI), considered, in general terms, as the result – not fixed, but dynamic – of the subject's immersion in teaching. Understanding that addressing the teachers' identities without demarcating the theoretical basis that supports and outlines the definition of this category can lead to inaccuracies or decontextualization, this article aims to discuss TPI from the concept of identity, in the sociological, psychosocial and professional perspectives. The proposed debate intends to contribute to research on teacher identity, considering the complexity of this object of study and demarcating fundamental elements of discussions on teachers' identity processes.